The Development of Community's Self-Understanding and the Meaning of Concept of Nation - Leonavičius, Vylius (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to discuss the relationship between the theoretical concepts and the historical experiences of a community the social sciences are a part of. The analysis is centered around the concepts of the nation and the folk and their relationship with the national self-understanding in Lithuania. The author attempts to show that the meaning of the two concepts is closely connected with the specific development of the Lithuanian state, its social stratification and cultural, social and political identity. The author suggests that the historical experience led to a distinction between the concepts of nation and folk that is widely accepted both in the everyday language and academic discourse.
Keywords: community's self-understanding; social science; concepts; nation and folk